MEASURING LOCAL GOVERNMENT CAPACITY IN TACKLING COVID-19 IN INDONESIA: THE CASE OF SUKABUMI CITY - Dewi - Wulandari; Rizki Hegia Sampurna; Andi Mulyadi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
Capacity is important to help government in facing COVID-19, because the government will be unable to absorb the COVID-19 problem when establishing strategy or policy if the capacity is lack. This study aims to measure how far local government capacity in tackling COVID-19, especially in Sukabumi City which is still facing the problem of COVID-19 cases. There are 8 criteria to measure local government capacity according to UNDP, namely: 1. Strategic Positioning, 2. Responsiveness, 3. Effective, 4. Efficient, 5. Sustainability, 6. Leadership, 7. Gender, 8. Coordination. The qualitative method with the case study approach was used in this research. The results showed that the capacity of local government has a significant impact, especially in tackling COVID-19. The capacity of Sukabumi City’s local bodies showed a good role with an improvement in reducing COVID-19 cases and has a strong coordination both with all element in Sukabumi City and with the central government, even though in some period has a significant case increased. However, several point must be fixed and improve related to the capacity of local government in tackling COVID-19 in Sukabumi City: (1) improve the quality of human resources, especially the health workers and secondly, (2) increase the community participation in order to compliance with all government policies, and (3) ensure the effectiveness and the efficiency of the COVID-19 programs and policies.